Transcedental Meditation: a Provocation against the Human Ego - Nikolov, Emmanuel (Forum Theologicum Sardicense, 2025)
The present research addresses aspects of the religious phenomenon of Transcendental Meditation. It proposes an Orthodox Christian perspective on the specific issue of moving away from the personalistic understanding prevalent in European Christian culture.